Watfa, Ägypten. Die Arbeiten des Jahres 2019 - Römer, Cornelia (e-Forschungsberichte des DAI, 2020)
A team of the German Archaeological Institute Cairo has been working in the Graeco-Roman village of Philoteris since 2011. Thanks to a splendid geomagnetic map, the layout of the village, including its water supply, is well known. After the discovery in 2017 of the first hellenistic gymnasium archaeologically attested in Egypt, the campaign focussed this year on the deeper understanding of water lifting facilities along the main canals, and the gymnasium with its race track for the stadium run. The development of this hellenistic institution into the Roman period as understood in this year’s campaign underlines the dramatic changes in Egypt between the Ptolemaic and Roman periods.